Recent Advances in the Use of Transglutaminase in Cheese Production - Warsono El Kiyat; Evlyn Laurenthia; Janice Michaela; Rizfi Fariz Pari (ASEAN Journal on Science and Technology for Development, 2021)
Various enzymes are used in the food industry to improve product quality. The enzyme transglutaminase is used to modify proteins in various foods through the formation of inter- and intramolecular epsilon-(gamma-glutamyl) lysine bonds. Previous studies have revealed that using transglutaminase in cheese production can increase the yield and enhance the characteristics of various types of cheese. However, the enzyme concentration, temperature, and pH influence the quality of cheese. This review aimed to discuss the potential of transglutaminase in cheese production. Our analysis showed that transglutaminase catalyzes the formation of covalent bonds between milk proteins (crosslinking), which results in a greater amount of casein trapped from whey and a higher yield of curd. Transglutaminase can also reduce production costs without negatively affecting cheese quality. These findings should prove useful in developing cheese products to improve consumer satisfaction.